THE ALBITE-WATER SYSTEM: PART III. CHARACTERIZATION OF LEACHED AND HYDROGEN-ENRICHED LAYERS FORMED AT 300°C USING MEV ION BEAM TECHNIQUES - Hellmann R.; Dran J.C.; Della Mea G. (My University, 1997)
Samples of albite feldspar were dissolved at 300°C and 170 bars for periods up to 24 h in flow-through reactors at acid, neutral, and basic pH conditions. Three MeV ion beam techniques, Resonant Nuclear Reaction Analysis (RNRA), Rutherford Backscattering Spectrometry (RBS), and Elastic Recoil Detection Analysis (ERDA) were employed to obtain elemental depth profiles and information on the composition of the near-surface region after dissolution. Based on the anti-correlative trends of the H and Na profiles obtained by RNRA, Na loss and H permeation are coupled by an ion exchange process in acidic and neutral pH solutions. At basic pH conditions, the evidence is ambiguous as to whether there is a limited degree of ion exchange between aqueous cations and Na, as based on RBS spectra and Na RNRA profiles.The recorded depths of H permeation and Na leaching range from a maximum at acid pH (H permeation exceeding ~10,000 #9, Na leaching ~20,000 #9) to a minimum at basic pH (no H enrichment, Na leaching depths of several hundred #9). The composition of the leached/H-enriched region is a function of pH. This is postulated to be primarily a function of two factors: the H ion concentration gradient between the solution and the solid, which directly controls the pH-dependence of the ion exchange couple H+ (or H3O+) # Na+, and secondly, the speciation of # Al -- OH and # Si -- OH groups created by hydrolysis reactions and the subsequent preferential release of Al within the leached/H-enriched zone. Based on the ratios of H uptake to Na loss at acid and neutral pH, which range between 0.7 and 2.5, it is not possible to distinguish between H+, H2O, and H3O+ species permeating into the structure. Free water may be created within the leached/H-enriched structure via recondensation (repolymerization) reactions of adjacent # Si -- OH groups. Excess H concentration profiles potentially provide indirect evidence for recondensation reactions at depths < 700 #9 during dissolution at acid pH conditions. Mass balance calculations, based on H permeation, Na loss, and Al preferential leaching, indicate that virtually no free H species (e.g., H2O molecules) are retained in the structure after dissolution at acid pH. This result also holds true for neutral and basic pH conditions of dissolution.